How can the migration of health service professionals be managed so as to reduce any negative effects on supply? - Buchan, James (World Health Organization, 2008)
The publication focuses on the migration of health personnel in Europe and the appropriate policy responses. Written for professionals.
European Observatory on Health Systems and Policies, ISSN 1997-8065 policy brief
Keywords: Health Workforce; zdravotničtí pracovníci; emigrace a imigrace; Health Personnel; poskytování zdravotní péče; Delivery of Health Care; Health Policy; zdravotní politika; management, organizace a řízení zdravotnictví; zahraniční odborný personál; Europe; Evropa; Emigration and Immigration; Foreign Professional Personnel; politologie, politika, zdravotní politika; zdravotnický personál